New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853 - Fateryga, Alexander V.; Mokrousov, Mikhail V. (Zootaxa, 2019)
New additions to the knowledge of the subfamily Eumeninae in Russia are provided. Leptochilus (Lionotulus) leleji Fateryga, sp. nov. is described from Altai Republic. Males of Ancistrocerus hangaicus Kurzenko, 1977 and Jucancistrocerus (Eremodynerus) minutepunctatus Giordani Soika, 1970 are described for the first time; the latter species is transferred from the nominotypical subgenus to the subgenus Eremodynerus Blüthgen, 1939. The genus Tachyancistrocerus Giordani Soika, 1952 and six species of eumenine wasps are reported from Russia for the first time: Discoelius pictus Kostylev, 1940a, Euodynerus (Euodynerus) curictensis Blüthgen, 1940, E. (E.) hellenicus Blüthgen, 1942, E. (E.) rufinus Blüthgen, 1942, Eustenancistrocerus (Eustenancistrocerus) jerichoensis (von Schulthess, 1928), and Tachyancistrocerus schmidti (Kokujev, 1913); E. hellenicus is also reported from Georgia and Azerbaijan. New regional records for nine species are reported. Three species are excluded from the fauna of Russia: Eustenancistrocerus (Eustenancistrocerus) tegularis (Morawitz, 1885), Odynerus (Odynerus) tristis (Blüthgen, 1939), and Stenodynerus aequisculptus (Kostylev, 1940b). The known fauna of Russia now numbers 34 genera and 162 species of eumenine wasps.